PEMBERDAYAAN MASYARAKAT DAN PENGEMBANGAN PARIWISATA BERBASIS UMKM DI DESA MALAKA, KABUPATEN LOMBOK UTARA - Habibi, Muazar; Psych, Psych; Ramadhan, Restu; Kresna, I Putu Dhimas Adi; Agustiani, Gifari; Dammi, Silvi Wiryan; Arianti, Chelmi Dwi; Sifani, Aulia Putri; Ramadhani, Salwa Nabilah; Maharani, Ni Putu Putri; Wirayudha, Arga; Faiza, Meyla (Jurnal Wicara, 2024)
Malaka Village, located in Pemenang District, North Lombok Regency, is a village with significant tourism potential, particularly through its stunning beaches. However, this potential has not been fully optimized, especially in terms of tourism product diversification and the development of micro, small, and medium enterprises (MSMEs). This article discusses the implementation of the Community Empowerment Service Learning Program (KKN PMD) aimed at empowering the residents of Malaka Village to develop their tourism potential and local MSMEs. The KKN activities include various programs in the fields of tourism, culinary arts, education, and environmental conservation, all of which are designed to support sustainable village development. Through a participatory approach, this program has successfully enhanced the community’s capacity to manage and promote local tourism, as well as to create culinary product diversification based on local marine resources. The results of this program show a significant increase in tourist visits and community income, as well as heightened environmental awareness among the villagers. Consequently, Malaka Village is expected to develop into a sustainable and widely recognized tourism village, both nationally and internationally.